Law and society reconsidered - Sarat, Austin (Amsterdam ; Oxford : Elsevier JAI, 2007)
This volume of "Studies in Law, Politics, and Society" presents a diverse array of interdisciplinary research. It contains articles by scholars from political science, sociology, and law. These articles examine the legal treatment of 'suspect' populations, the work of legal actors, and the works of various legal devices. Taken together the work published in this volume exemplifies the kind exciting and innovative work now being done by legal scholars from different disciplines. This book contains contributions from law and society scholars from political science, anthropology, sociology, and law and a comprehensive assessment of the state-of-the-field, its past, and its trajectory for the future.
Embracing eclecticism / Patricia Ewick -- Dr. Strangelove (or: how I learned to stop worrying and love methodology) / Michael McCann -- Precedents of injustice: thinking about history in law and society scholarship / Eve Darian-Smith -- Deconstructing law and society: a sociolegal aesthetics / Jonathan Goldberg-Hiller -- Would you like theory with that? : bridging the divide between policy-oriented empirical legal research, critical theory and politics / Rosemary Hunter -- International law and sociolegal scholarship: toward a spatial global legal pluralism / Sally Engle Merry -- Policing and the politics of public and private in post-Katrina New Orleans / Adelaide H. Villmoare -- Remorse and psychopathy at the penalty phase of the capital trial: how psychiatry's view of "moral insanity" helps build the case for death / Richard Weisman.
Description based on print version record.
Keywords: Sociological jurisprudence; Law & society; Social Science -- Sociology -- General; Political Science -- General